2022
DOI: 10.1017/ipm.2021.84
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal evaluation of the impact of the COVID-19 pandemic on a cohort of patients treated with clozapine

Abstract: Objectives: We previously demonstrated that three months into the COVID-19 pandemic, the impact on individuals with treatment-resistant psychotic disorders was modest. Here, we examined and compared the psychological and social impact of the COVID-19 pandemic on the same patient cohort 12 months after their initial study engagement. Methods: Semi-structured interviews were conducted with 54 individuals (85.7% response rate) between June 12 and July 29, 2021, 12 months after their initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, the longer-term veracity of this assertion was challenged on the grounds that data were collected during the nascent phase of COVID-19 (early 2020), where symptomatology was representative of an acute reaction/distress to an unknown, unexpected, and unfolding crisis (Daly and Robinson 2022). Subsequent studies revealed that some initial increase in symptoms at pandemic onset were not sustained, and declined significantly as the pandemic progressed, reverting to pre-pandemic levels within months of the initial outbreak (Bendau et al, 2021; Fancourt et.al, 2021; Robinson et al, 2022; Daly and Robinson 2021; Bartels et al, 2022; Daly and Robinson 2022), with longitudinal studies conducted at this site noting in individuals with pre-existing anxiety (this study cohort) and psychotic disorders, that anxiety symptoms remained at a relatively low level 6 and 12 months after the onset of the COVID-19 pandemic respectively (Hennigan et al, 2021; Rainford et al, 2022).…”
Section: Introductionmentioning
confidence: 85%
“…However, the longer-term veracity of this assertion was challenged on the grounds that data were collected during the nascent phase of COVID-19 (early 2020), where symptomatology was representative of an acute reaction/distress to an unknown, unexpected, and unfolding crisis (Daly and Robinson 2022). Subsequent studies revealed that some initial increase in symptoms at pandemic onset were not sustained, and declined significantly as the pandemic progressed, reverting to pre-pandemic levels within months of the initial outbreak (Bendau et al, 2021; Fancourt et.al, 2021; Robinson et al, 2022; Daly and Robinson 2021; Bartels et al, 2022; Daly and Robinson 2022), with longitudinal studies conducted at this site noting in individuals with pre-existing anxiety (this study cohort) and psychotic disorders, that anxiety symptoms remained at a relatively low level 6 and 12 months after the onset of the COVID-19 pandemic respectively (Hennigan et al, 2021; Rainford et al, 2022).…”
Section: Introductionmentioning
confidence: 85%
“…Many individuals with EUPD have a strong requirement for attachment including emotional and physical proximity to others (Aaronson et al 2006), thus the mandated requirements for social distancing might prove additionally difficult for this participant cohort. Fears of abandonment and rejection sensitivity (Poggi et al 2019) may additionally make restrictions difficult for this patient cohort. The impact of COVID-19 related social restrictions on health care delivery led to a reduction in available psychotherapeutic input (both within and outside mental health services) and where such therapeutic inputs continued, these were predominantly delivered utilising tele-communication fora.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several studies in individuals with major mental health disorders (i.e. anxiety and psychotic disorders) examining individuals at different time-points longitudinally since the onset of the COVID-19 pandemic have noted only a minimal increase in symptomatology, with impairments in social functioning most pronounced, however significant individual variation has been noted (Plunkett et al 2021;Hennigan et al 2021;McLoughlin et al 2023;Fahy et al 2021;Rainford et al 2022).…”
Section: Introductionmentioning
confidence: 92%
“…Another potential reason for the increased number of individuals actively engaged with MHS who presented with self-harm since the onset of the COVID-19 pandemic relates to increased referral rates to community MHS (College of Psychiatrists of Ireland 2020), with these increased case-loads potentially including many individuals who had previously engaged with MHS requesting additional supports due to the perceived and potential deleterious impact of the COVID-19 pandemic on their mental health. Whilst studies have previously have noted predominantly minimal deleterious consequences of the COVID-19 pandemic on active service users’ mental well-being, reduced social functioning and quality of life was reported (Fahy et al 2021; Hennigan et al 2021; Plunkett et al 2021; Rainford et al 2022); with MHS users with EUPD (associated with often higher rates of self-harm) experiencing the most significant impact on their mental well-being (McLoughlin et al 2021). These findings suggest an increase in distress in individuals attending MHS and may be reflected in some part in the increased rates of self-harm noted in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in individuals without pre-existing mental health disorders (including in Ireland) have noted an increase in psychiatric pathology, including higher levels of depressive and anxiety symptoms (Hyland et al 2020; Wang et al 2020). A relatively modest deleterious psychological impact of COVID-19 for individuals with pre-existing anxiety disorders (Plunkett et al 2020; Hennigan et al 2021), bipolar disorder (McLoughlin et al 2021), and schizophrenia (Fahy et al 2021; Rainford et al 2022) was previously demonstrated; with social functioning most impacted; however, individuals with a diagnosis of Emotionally Unstable Personality Disorder (EUPD) demonstrated both greater symptomatology and impaired social functioning (McLoughlin et al 2021).…”
Section: Introductionmentioning
confidence: 99%